Analysis of Perceptions and the Role of Local Leadership in Encouraging ODF Behavior - Lazarus Salyabo; Ratna Wardani; Agusta Dian Ellina (Universitas STRADA Indonesia, 2025)
Local leadership and community perceptions of the benefits of proper sanitation and the negative impacts of open defecation behavior can be a trigger for behavior change. Examining the analysis of perceptions and the role of local leadership in encouraging ODF behavior. A cross-sectional study was conducted in Mei 2023 on 224 people living in Dirwemna District, Yahukimo Regency. A simple random sampling was conducted to determine the respondent. Data was collected use a questionnaire and analyzed using regression. Research findings show that partially the perception of ODF (p=0.000) and local leadership (p=0.000) affect the open defecation free behaviour.